Potensi Tax Avoidance Terhadap Peraturan Pemerintah Nomor 23 Tahun 2018 Oleh Wajib Pajak Perseroan Terbatas - Suparna Wijaya; aditya setiawan (Owner : Riset dan Jurnal Akuntansi, 2021)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have an important role in encouraging the Indonesian economy, so the government provides tax facilities by issuing Government Regulation No. 46 of 2013 as has been replaced by Government Regulation No. 23 of 2018. Government Regulation No. 23 of 2018 excludes corporate taxpayers in the form of CV and firms that provide services in connection with independent work, while Limited Liability Companies do not. This study aims to explain the potential for tax avoidance in Government Regulation Number 23 of 2018 that can be carried out by Limited Liability Company taxpayers regarding income related to independent work, as well as the impact and solutions of such tax avoidance actions. The method used in this research is descriptive qualitative. The results of the study indicate that taxpayers who will establish a business entity with the type of business related to independent work, can choose to establish a Limited Liability Company compared to a CV or firm, so that they can use the relatively lower rate of Government Regulation Number 23 of 2018. This of course has an impact on reducing tax revenues, so the Directorate General of Taxes needs to minimize the potential for tax avoidance through education, supervision, and regulatory improvements.